Cardiorespiratory Events Associated With Ophthalmic Surgery: A Single-Center, Retrospective Records Review of 130 775 Patients, 1999–2015. (July 2020) - Singh, Vinodkumar; Bryant, Ayesha S.; Hull, Matthew; Skelley, Jason; Walters, Robin; Cross, R. Clark; Rozner, Marc A.; Boyd, Gwendolyn L.
Purpose: The most recent study of ophthalmic surgery morbidity and mortality was published in 1995, with a patient study population from 1977 to 1988. The present study reports surgical outcomes from a single-center, retrospective analysis of patient records from 1999 to 2015. Methods: Three International Classification of Diseases–9-CM codes for cardiorespiratory events were searched in the discharge diagnoses in an eye hospital over a 16-year period. The overall mortality and preoperative risk factors were analyzed, including the type of anesthetic, type of surgery, medical comorbidities, and bradycardia preceding the cardiac events. Results: Between February 1, 1999 and October 1, 2015, a total of 130 775 patients presented for ophthalmic surgery. Fifty-nine patients (0.45 per 1000) experienced a cardiorespiratory event. Of the 59 patients, 14 patients had a cardiorespiratory arrest, 9 of whom died during the perioperative period. Of the remaining 45 patients, 29 had significant adverse events needing some form of advanced monitoring, evaluation, and/or intervention. There was a significantly greater prevalence of diabetes among patients who had a cardiorespiratory event ( P < .001). Conclusions: The major risk factor associated with ophthalmic surgery morbidity and mortality was diabetes with its associated complications of autonomic neuropathy, nephropathy, and retinopathy. Of the 9 patients who died, 8 were diabetic with proliferative diabetic retinopathy and renal insufficiency/failure. The ninth mortality was secondary to a venous air embolism during ocular air infusion. The adage that "the eye is the window to our overall health" seems to be correct.